Automation of testing modules of controller ELSY-ТМК; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Dolotov A. E. Aleksandr Evgenievich; Petuhov D. V.; Potapova A. P.; Dolotova R. G. Raisa Grigorievna (2017, 2017)
Title screen